Philip DuMont letter to Joseph Grinnell regarding Savannah Sparrow identification, November 6, 1933 - DuMont, Philip A. (Philip Atkinson), 1903-1996 (1933)
Letter from Philip DuMont to Joseph Grinnell dated November 6, 1933. DuMont asks for assistance in correctly identifying Savannah Sparrow specimens and mentions that the Revised list of the birds of Iowa should be available in about two weeks. This document is answered by a letter from Grinnell: https://n2t.net/ark:/87292/w9z60c19d.